2020
DOI: 10.1093/tas/txaa066
|View full text |Cite
|
Sign up to set email alerts
|

Effects of timing and size of meals prior to farrowing on sow and litter performance

Abstract: A total of 727 mixed parity (µ = 3.8) sows were used to evaluate the effects of timing and size of meals before farrowing on sow and litter performance. Upon entry to the farrowing house (day 113), sows were blocked by weight within parity and allotted to one of three three feeding management strategies until farrowing: (1) 2.7 kg lactation diet (1.15% standardized ileal digestible lysine and 2,153 kcal/kg net energy) once daily at 0700 hours; (2) four daily meals of 0.67 kg (0100, 0700, 1300, and 1900 hours);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
2
18
1
Order By: Relevance
“…It has been observed that a longer farrowing duration is associated with an increased piglet stillborn rate [45,46]. However, there was no evidence for a difference in the stillborn rate in this study, regardless of the feeding system.…”
Section: Discussioncontrasting
confidence: 73%
“…It has been observed that a longer farrowing duration is associated with an increased piglet stillborn rate [45,46]. However, there was no evidence for a difference in the stillborn rate in this study, regardless of the feeding system.…”
Section: Discussioncontrasting
confidence: 73%
“…Hence, these factors may also be associated with dystocia. More importantly, the categorization of prolonged birth interval as part of dystocia will establish an easy guide for when to apply obstetric intervention to assist sows and piglets [ 2 , 8 , 9 ], thereby reducing the stillbirth rate.…”
Section: Introductionmentioning
confidence: 99%
“…The coefficient of variation of TNB and NBA were larger, about 27%. Significant difference was not found in FAR between different TNB, but found between different NBA because of the interact between FAR and stillbirth [ 19 ]. Shortening the length of FAR will not reduce the effective NBA.…”
Section: Discussionmentioning
confidence: 99%